2016
DOI: 10.1016/j.polymdegradstab.2016.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Impact of hydrothermal ageing on the thermal stability, morphology and viscoelastic performance of PLA/sisal biocomposites

Abstract: The influence of the combined exposure to water and temperature on the behaviour of polylactide/sisal biocomposites coupled with maleic acid anhydride was assessed through accelerated hydrothermal ageing. The biocomposites were immersed in water at temperatures from 65 to 85 ºC, between the glass transition and cold crystallisation of the PLA matrix. The results showed that the most influent factor for water absorption was the percentage of fibres, followed by the presence of coupling agent, whereas the effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 57 publications
12
34
0
Order By: Relevance
“…The evolution of XC is given in Figure 7 for all biocomposites subjected to biodegradation in soil. Neat PLA showed very low XC, due to its amorphous character, in agreement with previous studies [6], [7].…”
Section: Impact Of Biodegradation In Soil On the Morphology And Thermsupporting
confidence: 92%
“…The evolution of XC is given in Figure 7 for all biocomposites subjected to biodegradation in soil. Neat PLA showed very low XC, due to its amorphous character, in agreement with previous studies [6], [7].…”
Section: Impact Of Biodegradation In Soil On the Morphology And Thermsupporting
confidence: 92%
“…Table 5 summarizes the values of degradation temperature at 5 wt% loss (T 5% ) and 50 wt% loss (T 50% ) with exposure time. It is observed that T 5% of PLA fibers decreased significantly at 60 • C, while T 50% was almost unchanged, particularly at 45 • C. This is in a good agreement with the data published by Gil-Castell et al (2016) who reported that the temperature at maximum degradation rate of PLA and PLA/sisal biocomposites remains constant after hydrolysis in water at 85 • C, while the onset degradation temperature decreases significantly. Table 5 shows also that after 14 days at 60 • C, T 5% decreased considerably by 22, 52, and 56 • C for neat PLA, PLA/PLA-g-MA/MCC1, and PLA/PLA-g-MA/CNW1, respectively.…”
Section: Thermal Stabilitysupporting
confidence: 91%
“…The PLA–tegument sample fracture surface, in Figure (c), displays a homogeneous PLA matrix, as also fiber bundles and tails randomly distributed over the surface. In addition, there is no distinguishable interface between the tegument's fibers and PLA, since the PLA's polarity contributes to the affinity between PLA and cellulose fibers . The PLA–almond–tegument samples [Figure (d)] show, as expected and mentioned before, the noncompatibility between the starch and PLA phases and the adhesiveness between PLA and cellulose fibers.…”
Section: Resultssupporting
confidence: 62%